French invasive Asian tiger mosquito populations harbor reduced bacterial microbiota and genetic diversity compared to Vietnamese autochthonous relatives - Minard, Guillaume; TRAN, Florence-Hélène; tran-van, van; Goubert, Clement; Bellet, Christophe; Lambert, Grégory; Khanh, Huynh Kim Ly; Huynh, Trang; Mavingui, Patrick; Valiente Moro, Claire (Frontiers in Microbiology, 2015)
The Asian tiger mosquito Aedes albopictus is one of the most significant pathogen vectors of the 21st century. Originating from Asia, it has invaded a wide range of eco-climatic regions worldwide. The insect-associated microbiota is now recognized to play a significant role in host biology. While genetic diversity bottlenecks are known to result from biological invasions, the resulting shifts in host-associated microbiota diversity has not been thoroughly investigated. To address this subject, we compared four autochthonous Ae. albopictus populations in Vietnam, the native area of Ae. albopictus, and three populations recently introduced to Metropolitan France, with the aim of documenting whether these populations display differences in host genotype and bacterial microbiota. Population-level genetic diversity (microsatellite markers and COI haplotype) and bacterial diversity (16S rDNA metabarcoding) were compared between field-caught mosquitoes. Bacterial microbiota from the whole insect bodies were largely dominated by Wolbachia pipientis. Targeted analysis of the gut microbiota revealed a greater bacterial diversity in which a fraction was common between French and Vietnamese populations. The genus Dysgonomonas was the most prevalent and abundant across all studied populations. Overall genetic diversities of both hosts and bacterial microbiota were significantly reduced in recently established populations of France compared to the autochthonous populations of Vietnam. These results open up many important avenues of investigation in order to link the process of geographical invasion to shifts in commensal and symbiotic microbiome communities, as such shifts may have dramatic impacts on the biology and/or vector competence of invading hematophagous insects.